Prabhã - Mandala: os efeitos da aplicação do desenho da mandala no comportamento da atenção concentrada em adolescentes - Dibo, Monalisa (2007)
The purpose of this study consists in the determination of whether the mandala's design improves concentrated attention in teenagers in a classroom, and if it presents symbols of religious connotation. This is a quantitative as well as a qualitative research project, focusing on the quantity and frequency of the meanings and processes under scrutiny. The tool used for the mensuratiion of concentrated attention in four high school groups, totalling 70 teenagers, was Test AC-15. In the concentrated attention test, groups B and C (mandala + test) showed results above the average, while groups D and E (test + mandala) came up with results below the average; thus attesting to the mandala's improvement of concentrated attention. The results also show that circular forms are the most frequent in the mandala's inwards, and that, in the quadrature of the circle, flower and star shapes prevail among the themes found. In the verification and analysis of the groups, it is possible to observe that the drawings, in their majority, are center-aligned, which indicates that the subjects of this research are well-adjusted individuals, with a tendency to be more self-driven and self-centered. The characteristics of drawing styles and pressure, reflecting emotional and mental balance, appear to be normal. Also, the drawings present mostly average aesthetic results, showing signs of intelligence, aptitude for spatial abstraction, and emotional equilibrium. Therefore, it can be said that, in this study, the mandala presented an enriching activity for individuals' psychic life, enhancing concentrated attention in the subjects, and bringing moments of improvement in the inner contact with order and harmony, leading to emotional integration